Office Christmas party [videorecording (DVD)] - Bateman, Jason; Munn, Olivia, 1980-; Miller, T. J., 1981-; Aniston, Jennifer (Paramount Pictures Corporation, 2017)
When the CEO tries to close her hard-partying brother's branch, he and his Chief Technical Officer must rally their co-workers and host an epic office Christmas party in an effort to impress a potential client and close a sale that will save their jobs.